Understanding of the Gricean maxims in children with autism spectrum disorder: Implications for pragmatic language development. (August 2022) - Asada, Kosuke; Itakura, Shoji; Okanda, Mako; Moriguchi, Yusuke; Yokawa, Kaori; Kumagaya, Shinichiro; Konishi, Kaoru; Konishi, Yukuo
Abstract: Children with autism spectrum disorder (ASD) often have difficulties in communication with others, which may derive from limitations in their understanding of pragmatic language. In this study, we used the Conversational Violations Test (CVT) with children with ASD and typically developing (TD) children in order to examine their sensitivity to violations of the Gricean maxims: be relevant (maxim of Relation), be truthful (maxim of Quality), be informative (Quantity I), avoid redundancy (Quantity II), and be polite (maxim of Politeness). These maxims have an important role in communication. We found that TD children performed better than children with ASD on the CVT. We also found that children with ASD had higher total CVT scores with increasing chronological age. We discuss the developmental trajectories of pragmatic language understanding in children with ASD. Highlights: Understanding of the Gricean maxims was assessed with the CVT. TD children performed better than children with ASD on the CVT. Children with ASD had higher total CVT scores with increasing chronological age.